Anserine and Carnosine induce HSP70-dependent H2S formation in endothelial cells and murine kidney - Wetzel, Charlotte; Pfeffer, Tilman; Bulkescher, Ruben; Zemva, Johanna; Modafferi, Sergio; Polimeni, Alessandra; Trovato, Angela; Calabrese, Vittorio; Schmitt, Claus P.; Peters, Verena (Antioxidants, 2023)
Anserine and carnosine have nephroprotective actions; hydrogen sulfide (H2S) protects from ischemic tissue damage, and the underlying mechanisms are debated. In view of their common interaction with HSP70, we studied possible interactions of both dipeptides with H2S. H2S formation was measured in human proximal tubular epithelial cells (HK-2); three endothelial cell lines (HUVEC, HUAEC, MCEC); and in renal murine tissue of wild-type (WT), carnosinase-1 knockout (Cndp1-KO) and Hsp70-KO mice. Diabetes was induced by streptozocin. Incubation with carnosine increased H2S synthesis capacity in tubular cells, as well as with anserine in all three endothelial cell lines. H2S dose-dependently reduced anserine/carnosine degradation rate by serum and recombinant carnosinase-1 (CN1). Endothelial Hsp70-KO reduced H2S formation and abolished the stimulation by anserine and could be restored by Hsp70 transfection. In female Hsp70-KO mice, kidney H2S formation was halved. In Cndp1-KO mice, kidney anserine concentrations were several-fold and sex-specifically increased. Kidney H2S formation capacity was increased 2-3-fold in female mice and correlated with anserine and carnosine concentrations. In diabetic Cndp1-KO mice, renal anserine and carnosine concentrations as well as H2S formation capacity were markedly reduced compared to non-diabetic Cndp1-KO littermates. Anserine and carnosine induce H2S formation in a cell-type and Hsp70-specific manner within a positive feedback loop with CN1.
Im Titel ist 2 tiefgestellt
Gesehen am 22.03.2023
Published: 28 December 2022